2022
DOI: 10.20517/jmi.2022.23
|View full text |Cite
|
Sign up to set email alerts
|

High-entropy alloy catalysts: high-throughput and machine learning-driven design

Abstract: High-entropy alloy (HEA) catalysts have recently attracted worldwide research interest due to their promising catalytic performance. Most current studies focus on designing HEA catalysts through trial-and-error methods. This produces scattered data and is not conducive to obtaining a fundamental understanding of the structure-property-performance relationships for HEA catalysts, thereby hindering their rational design. High-throughput (HT) techniques and machine learning (ML) methods show significant potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 84 publications
0
2
0
Order By: Relevance
“…It sustains long‐term stability upon HER and OER, [78] demonstrating the feasibility of HEA and MEA in electrocatalytic fields. Similar studies are also reported in FeCoNiMnW, [79] NiCoFeMoMn, [80] CuAlNiMoFe [27] ect [76,81] . By implementing machine learning and DFT calculations, Saidi et al [82] .…”
Section: Machine Learning Accelerating the Potential Discovery Of Her...supporting
confidence: 56%
See 2 more Smart Citations
“…It sustains long‐term stability upon HER and OER, [78] demonstrating the feasibility of HEA and MEA in electrocatalytic fields. Similar studies are also reported in FeCoNiMnW, [79] NiCoFeMoMn, [80] CuAlNiMoFe [27] ect [76,81] . By implementing machine learning and DFT calculations, Saidi et al [82] .…”
Section: Machine Learning Accelerating the Potential Discovery Of Her...supporting
confidence: 56%
“…But with the increase of the metal elements in the HEA, the constructed systems tend to increase sharply, thus enlarging the potential candidates for them in various functional materials fields. ML strategy offers a convenient method to search for excellent candidates among a vast of constructed data, which has been widely utilized in recent years for high throughput screening [73–77] . For the HER, the constructed HAE and MEA reduce the usage of Pt and offer diverse adsorption sites for H, thus leading to various sites exhibiting different adsorption energy for HER, which enhances the HER activities.…”
Section: Machine Learning Accelerating the Potential Discovery Of Her...mentioning
confidence: 99%
See 1 more Smart Citation
“…HT techniques can achieve more automated, parallel, and efficient HEA research. 224 Singh et al employed ML and DFT to predict the adsorption free energy of key reaction intermediates on HEAs, thereby quantitatively unifying the ligand (element identity) and coordination (surface structures) effects for HEA catalysts. A neural network (NN) model was utilized to evaluate the OH* adsorption energy over the IrPdPtRhRu HEA catalyst.…”
Section: Rational Design Of Heas With Industrial Application Prospectsmentioning
confidence: 99%
“…It is also worth noting that the experimentally studied compositional libraries are often narrowed by preliminary theoretical calculations using DFT, MD, ML, or CALPHAD methods. [16][17][18][19][20][21][66][67][68][69] However, this study focuses on the experimental part of the combinatorial design of MPEAs; therefore, only a brief overview of this theoretical field is given here. The high-throughput computational techniques can help to identify the compositions promising from the point of view of application demands, thereby reducing the time and effort invested in the experimental investigations.…”
Section: Complementary Theoretical Approaches Of Combinatorial Design...mentioning
confidence: 99%